Golf Courses' Water Use and Conservation Practices in Miami-Dade County - Rafael Muñoz-Carpena; Jonathan H. Crane; Glenn D. Israel; Charles Yurgalevitch (EDIS)
This fact sheet reports water conservation trends from golf course managers based on an extensive survey carried out in Miami-Dade County. This document is Fact Sheet ABE348, one of a series of the Agricultural and Biolgoical Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2004.